Association of Heart Transplant Volume with Presence of Lung Transplant Programs and Heart Transplant’s SRTR One-year Survival Rating - Rosen, Jake L.; Ahmad, Danial; Uphadyaya, Anjali; Brodie, Andrew T.; Gaw, Gabriel; Rajapreyar, Indranee; Rame, J. Eduardo; Alvarez, Rene J.; Rajagopal, Keshava; Entwistle, John W.; Massey, Howard T.; Tchantchaleishvili, Vakhtang (The Thoracic and Cardiovascular Surgeon, 2023)
Background Several factors affect heart transplant (HTx) and lung transplant (LTx) program outcomes. Variabilities in institutional and community characteristics have been shown to influence survival. At present, half of HTx centers in the United States do not possess a concomitant LTx program. This study sought to better understand the characteristics of HTx with and without LTx programs.Methods Nationwide transplant data were collected from the Scientific Registry of Transplant Recipients (SRTR) in August 2020. SRTR star rating ranges from tier 1 (lowest) to tier 5 (highest). HTx volumes and SRTR star ratings for survival were compared between the centers with heart-only (H0) programs and the centers with heart-lung (HL) programs.Results SRTR star ratings were available for 117 transplant centers with one or more HTx reported. The median number of HTx performed over 1 year was 16 (interquartile range [IQR]: 2–29). The number of HL centers (n = 67, 57.3%) were comparable to H0 centers (n = 50, 42.7%; p = 0.14). The HTx volume at the HL centers (28 [IQR: 17–41]) exceeded the HTx volume at the H0 centers (13 [IQR: 9–23]; p < 0.01), but were comparable to the LTx volume at the HL centers (31 [IQR: 16–46]; p = 0.25). The median HTx one-year survival rating was 3 (IQR: 2–4) at both the H0 and HL centers (p = 0.85). The HTx and LTx volumes were positively associated with the respective 1-year survivals (p < 0.01).Conclusion While the presence of an LTx program is not directly associated with HTx survival, it has a positive association with the HTx volume. The HTx and LTx volumes are positively associated with the 1-year survival.
Keywords: cardiac transplantation; heart transplantation; lung transplantation; survival; outcomes